O que sabemos sobre os bebês? uma revisão de literatura sobre a emergência da Teoria da Mente - Silva, Caroline Campos Rodrigues da (2018)
The ability to infer what other people think and to identify the intentionality of actions is defined as theory of mind, which is a useful cognitive ability to the adaptation within the social world, since it is proper from the human being to regulate a considerable part of their actions based on the knowledge about the intentions of others This study aims to review articles about the emergence and development of the theory of mind in infants. The search was was conducted in Science Direct, Scielo and PsycNet, obtained 399 results, which 46 articles were analyzed regarding to the development of theory of mind before expressive language. The analysis led to five thematic categories: (a) theoretical articles about the development and emergence of theory of mind; (b) articles regarding the development of false belief; (c) implications of the kind of parental care to the development of theory of mind; (d) studies about intentional communication and (e) studies about the comprehension of mental states. It was possible to ascertain that a great part of these researches were about children between 13 and 18 months. The results also suggest lack of consensus among researchers regarding to the moment when the theory of mind emerges or when it actually becomes a theory